Blood Biochemistry Reference Values of Javan Slow Loris (Nycticebus javanicus) in Rehabilitation Center - Nur Purba Priambada; Indri Saptorini; Imam Arifin; Wendi Prameswari; Karmele Llano-Sanchez (IPB University, 2021)
The Javan slow loris (Nycticebus javanicus) is an endemic primate species to Java Island, Indonesia. Currently, their conservation status is critically endangered due to habitat loss and the illegal wildlife trade. As a consequence of the pet trade, wild-caught slow lorises are confiscated or handed over to centers like IAR Indonesia Rescue Center. Rescued lorises present multiple health issues following stress, trauma, and miss-treatment after being kept as pets. During the medical evaluation, besides physical examination, blood biochemistry provides valuable diagnostic information. However, data on physiological values are unavailable and therefore interpretation of results is difficult. The objective of this study was to establish blood biochemistry reference values for wild, rehabilitant healthy adult Javan slow lorises in captivity. We anesthetized 20 individuals of Javan slow loris (10 males and 10 females) for pre-release check-up procedures. Blood samples were collected for blood biochemistry analysis on an in-house Vetscan VS2 (Zoetis), after which the results were statistically analyzed for mean and standard deviation. Results showed different values between the male and female group, however, they were not significant (p>0,05). Comparison with available biochemistry data (ZIMS) for other loris species in captivity: Nycticebus pygmaeus and Nycticebus coucang, did not show significant differences. Although the sample size of this study was limited, this study provides the first preliminary reference ranges for healthy adult wild, rehabilitant Javan slow loris in captivity. Further data collection is necessary for more accurate ranges and will be done during the future pre-release health check.